ANALISIS PENDAPATAN INDUSTRI KERAJINAN ENCENG GONDOK TERHADAP TOTAL PENDAPATAN RUMAH TANGGA PENGRAJIN (Studi Kasus di Desa Kludan Kecamatan Tanggulangin Kabupaten Sidoarjo) - Suhardi, Natalia; Syahrial, Ramon (Fakultas Pertanian Universitas Wijaya Putra, 2024)
The purpose of this study was to determine the(1) The process of processing water hyacinth handicraft industry so that it becomes a handicraft. (2) The obstacles experienced by water hyacinth craftsmen. (3) Craftsmen's efforts to overcome obstacles to the water hyacinth craft industry. (4) Income contribution from the water hyacinth craft industry. (5) Efforts to develop the self-development of craftsmen in the water hyacinth craft industry. This research is a quantitative research in which the research subjects were craftsmen's households in Kludan Village, Tanggulangin District, Sidoarjo Regency with 50 respondents and it was a population study. The data collection techniques are observation, interviews and documentation. The data analysis used is quantitative descriptive. The results showed that: (1) The processing of the water hyacinth handicraft industry in Kludan Village, Tanggulangin District, Sidoarjo Regency is still in the form of semi-finished goods, the raw material price is IDR 4,500/kg. Water hyacinth craft products include: bags, pillows, prisms, mats, and others. The price of water hyacinth crafts ranges from IDR 8,000 – IDR 30,000 depending on the size of the craft item. (2) The obstacles experienced by craftsmen are expensive raw materials, craftsmen are not given the opportunity to process water hyacinth crafts until the finishing stage. (3) Efforts to overcome obstacles, namely craftsmen learn to process water hyacinth crafts until the finishing stage to increase the price of water hyacinth crafts by forming groups. (4) The contribution of income from water hyacinth crafts to the total household income of craftsmen is 27.5%. (5) Efforts to develop self-development of water hyacinth craft industry craftsmen, namely craftsmen taking courses or training, conducting promotions or exhibitions to introduce water hyacinth crafts.